Comparing Technology Acceptance for Electric Vehicles – A Comparative Study in Turkey and Germany - Özdemir-Öztürk, Nazan; BARUTÇU , Süleyman (International Journal of Contemporary Economics and Administrative Sciences, 2022)
Climate change, environmental concerns, scarcity of resources and dependence on energy cause the automotive industries to do sustainable developments. İn this regard, the adoption of new energy vehicles is key to environmental problems. The objective of this study is twofold, to understand consumer’s intentions regarding electric vehicles (EV) adoption and secondly to compare these results for developing and industrialized/ developed “Western” countries, Turkey and Germany. An empirical study was carried out with 557 potential consumers in Turkey and 513 in Germany and structural equation analysis was performed with AMOS. An integrated model based on Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM) is applied as the research framework. The paper confirms the underlying assumptions of TAM in the context of EV. Perceived usefulness (PU) and perceived ease of use (PEOU) positively influence the behavioral intention to use EVs. TAM constructs were found to be statistically significant. The results showed that participants' technology acceptance attitudes differed by country. Behavioral usage intentions of participants living in Germany are higher than those in Turkey. Based on the empirical results, the formulation of marketing strategies to promote EV and suggestions for future research are discussed.